Current Conditions and Desirable Needs of Research Management to Enhance Research and Innovation Capabilities of Maritime Higher Education Institution - Rojmanawong, Tanaruj; Yongsorn, Chatupol; Ponathong, Chakrit (Rajapark Journal, 2023)
The purposes of this research are as follows: 1) to study the best practices of research management from 9 Thai National Research Universities and maritime higher education institution in Thailand and abroad; 2) to study the modified priority needs index of research management to enhance research and innovation capabilities of maritime higher education institution. It’s a mixed methodology research. Qualitative research, the researcher used a semi-structured in-depth interview from 9 executives and heads of maritime higher education institutions and research centers. Quantitative research, the researcher used the need assessment questionnaire to collect data from 123 lecturers, academics, and staff. The statistics used in the data analysis were frequency, mean, standard deviation, and modified priority needs index (PNImodified) to synthesize and prioritize research management to enhance the research and innovation capabilities of maritime higher education institution. The finding from the best practice study and in-depth interviews consists of 6 components, ranked in order of the modified priority index as follows: 1) grants followed by 2) researchers and research development 3) the network link 4) organization and infrastructure 5) research and innovation results and 6) research and innovation policy.